HUBUNGAN FAMILY SUPPORT DENGAN TINGKAT KECEMASAN DAN STRESS PASIEN POST PERCUTANEOUS CORONARY INTERVENTION (PCI) DI MURNI TEGUH MEMORIAL KOTA MEDAN - Siahaan, Lina Magdalena; Tambunan, Dior Manta (STIKes Murni Teguh, 2025)
Coronary heart disease patients require Percutaneous Coronary Intervention (PCI) to remove blockages in the coronary artery blood, so that blood flow can return to normal. Although PCI has a relatively low risk, patients still feel anxious and stressed post PCI. This is thought to be due to lack of family support. The purpose of this study was to determine the relationship between family support with anxiety and stress levels of Post PCI patients. This study is a quantitative study with a correlational study design using a cross-sectional approach. The study was conducted at Murni Teguh Memorial Hospital. The sample in this study amounted to 92 respondents with purposive sampling technique. Data analysis used the Spearman Rho and Anova test. The result of this study with the spearman test showed a relationship between family support with anxiety and stress levels of Post PCI as indicated by a p-value <0.05. The anova test explains that there is a relationship between family support with anxiety of Post PCI patients as indicated by p-value <0.05 and there is no relationship between family support with stress level as indicated by p-value >0.05. It is recommended for further researchers to conduct research by adding individual coping variables and health worker support.